The Effectiveness of Implementing the Independent Curriculum in Shaping an Innovative Generation in Indonesia - Vitasari, Dian; Noviani, Dwi; Anggraini, Lisa; Safitri, Desy; Hile, Abdulhafiz (The Islamic Education and Multiculturalism Foundation, 2025)
Abstrak The Independent Curriculum, as one of the government's efforts to improve the quality of education in Indonesia, is expected to produce a generation that is innovative and adaptable to the changing times. This study aims to analyze the effectiveness of the implementation of the Independent Curriculum in shaping an innovative generation in Indonesia. Using a qualitative approach, this research involves teachers, students, and school principals as informants. The findings indicate that the Independent Curriculum holds significant potential in shaping an innovative generation. The curriculum's flexibility allows teachers to tailor learning materials to students' interests and talents, while also promoting active and student-centered learning. Furthermore, the project-based learning characteristic of the Independent Curriculum provides opportunities for students to develop creativity and problem-solving skills. However, the implementation of the Independent Curriculum faces several challenges, including insufficient teacher preparedness, limited facilities and infrastructure, and a lack of coordination among stakeholders. Therefore, more intensive efforts are needed to address these challenges to ensure the Independent Curriculum can be implemented effectively and optimally.